Self assessment System Dalam Transaksi E-Commerce Era 5.0 - Aliuk, Stefania Sri Putri; Hardiningsih, Pancawati (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
To promote taxpayer compliance, self-assessment is being used in e-commerce transactions as part of research project 5.0. MSMEs in the Kupang region that sell online make up the study's sample. Data was gathered via a Google Form-based online survey. The analytical method is straightforward linear regression. According to the study's findings, the introduction of self-assessment has a considerable impact on taxpayer compliance.